Pengaruh Celebrity Endorsment, Citra Merek dan Kepercayaan Merek Terhadap Niat Beli Produk Serum Somethinc di Instagram : indonesia - lita; Mahardhika, Miranda; Fadli, Jul Aidil (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
Currently in Indonesia, it has become a trend to use skincare, especially serum in carrying out treatments to have beautiful and beautiful skin to support appearance. To ensure the attractiveness and satisfaction of the online media for the beauty business, the researchers tried to find out in depth about the reviews of the use of celebrity endorsements. So in an effort to maintain the positive impact of celebrity endorsements on Instagram on customer behavior, researchers and business experts are encouraged to have a better understanding of this phenomenon. In this study, researchers examined the effect of celebrity endorsements on the purchase intention of beauty serum products on Instagram. In analyzing the data, the researcher used simple regression analysis to determine the effect partially, while multiple regression analysis was used to determine the effect simultaneously. Furthermore, this study uses primary data obtained from distributing questionnaires to 160 respondents ranging from 15 to 50 years of age who know the SomeThinc brand and celebrity Tasya Faraysa on Instagram. The results of this study prove that celebrity endorsement has a positive effect on brand image and brand trust and purchase intention, then brand trust and brand image also have a positive effect on purchase intention, this means that brand trust and brand image can strengthen the influence of celebrity endorsement on purchase intention.